The Effectiveness Of Project Based Learning On Critical Thinking Abilities And Character Of Elementary School Students In Science Learning - Fahmi, Fahmi; Hidayati, Arini Ulfah; Rohman, Miftahur (Universitas Islam Negeri Raden Intan Lampung, 2026)
This study aims to test the effectiveness of Project Based Learning (PjBL) on critical thinking skills and character development in elementary school students. This study used a quasi-experimental method with a nonequivalent pretest–posttest design group design. The study population consisted of fifth-grade students of Indrasari 1 Public Elementary School, Martapura District, Banjar Regency, South Kalimantan, consisting of three classes. Two classes were randomly selected as research samples, namely class VA as the experimental class implementing PjBL and class VC as the control class, each consisting of 35 students. Data analysis was carried out using one sample t-test, MANOVA with Hotelling's T² criteria, and independent t-test. The results of the assumption test showed that the data met the analysis requirements, both multivariate normality (sig. 0.12–0.86 > 0.05), multivariate homogeneity (Box's M pretest = 4.161; sig. = 0.087 and posttest = 2.906; sig. = 0.840), univariate normality (sig. 0.07–0.20 > 0.05), and homogeneity of variance (critical thinking ability sig. = 0.430; character sig. = 0.671). The MANOVA results before treatment showed no difference in the initial mean between the two groups (Hotelling's T² = 0.016; F = 0.546; sig. = 0.582 > 0.05). The results of the study showed that PjBL learning was effective in improving students' critical thinking skills and character, compared to conventional learning